SOME PROBLEMS CONCERNING THE IMPLEMENTATION OF THE SURROGATE MATERNITY IN THE REPUBLIC OF ARMENIA - Artashesyan, Naira (State and Law, 2021)
In this paper, we have presented the deficiencies and problems of the legal regulation of the maternity institution. Today, many contracts of surrogate maternity are concluded in practice without the understanding of its legal significance and consequences. The law has a very broad definition about this important issue, since practically no part of the contract of maternity  is legally protected. Generally, the question is whether the medical establishment should treat biological parents with whom it has contracted, or should there be any limitations in the case, whether there is any state body that oversees the signing of these contracts? Today, no one is responsible for the conclusion of these contracts, which is an urgent problem as this area is too risky, and first of all the state should think about protection oh interests of the newly born child because very often the child can become a buying and selling subject, which is inadmissible from the moral viewpoint.We have tried to answer all the questions in the context of this scientific article from the legal point of view by analyzing the domestic and international legislations.
Keywords: surrogate; maternity treaty; reproductive rights; embryo; child rights; genetic donor